Dampak Perilaku Konsumen Terhadap Produk Lokal di Pasar Tradisional Kota Ende - Maria Leliana Bhenge; Helena Rosalia Parera (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
This study aims to analyze the impact of consumer behavior on local products in traditional markets in Ende City, using a qualitative descriptive approach. Data were collected through interviews, observation, and documentation. Data were then analyzed using the Miles and Hubermen interactive analysis method. The study subjects included ten person in three traditional markets in Ende City: Mbongawani Market, Potulando Market, and Wolowona Market. The results indicate that consumer behavior has a significant impact on the sustainability of local products, with cultural awareness, price, quality, and access being the main determinants of purchasing decisions. The findings indicate that consumers with a high awareness of local products tend to support the economic sustainability of small traders and cultural preservation. However, challenges and shifts in consumer lifestyles create resistance to local products in traditional markets.